2021
DOI: 10.3390/ijerph18115735
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 4th of July Fireworks on Spatiotemporal PM2.5 Concentrations in California Based on the PurpleAir Sensor Network: Implications for Policy and Environmental Justice

Abstract: Fireworks are often used in celebration, causing short term, extremely high particulate matter air pollution. In recent years, the rapid development and expansion of low-cost air quality sensors by companies such as PurpleAir has enabled an understanding of air pollution at a much higher spatiotemporal resolution compared to traditional monitoring networks. In this study, real-time PM2.5 measurements from 751 PurpleAir sensors operating from June to July in 2019 and 2020 were used to examine the impact of 4th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Some scholars believe that it may affect the stock market, the performances of companies, and so on [42,43]. At the theoretical level, the basis for policy evaluation has been relatively rich, but a review of the literature shows that environmental policies are not sufficiently evaluated [44,45]. Although the interview system has been applied in many fields, research on it has been qualitative.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars believe that it may affect the stock market, the performances of companies, and so on [42,43]. At the theoretical level, the basis for policy evaluation has been relatively rich, but a review of the literature shows that environmental policies are not sufficiently evaluated [44,45]. Although the interview system has been applied in many fields, research on it has been qualitative.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Dylos may be used as a simple low-cost substitute for gravimetric analysis when measuring fine particles, such as second-hand cigarette smoke or ambient air pollution ( Semple et al , 2015 , Carvlin et al , 2017 , Ferdous et al , 2020 ). Similarly, PA has been used to measure fine particle ambient air pollution in various settings ( Mousavi et al , 2021 ). Moreover, we found the use of the Dylos counter particularly problematic since larger cotton particles (‘fluff’) tended to choke the device’s internal fan, necessitating frequent cleaning during field sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Some widely adopted sensors include the Plantower PMS series (module used in a variety of integrated sensor systems, such as PurpleAir), Alphasense OPC-N2, Panasonic PM2.5 sensors, NovaFitness SDS, Shinyei PPD series, Samyoung DSM series, and Sharp GP and DP series. Those sensors have been used under various scenarios, such as environmental regulation (Bi et al, 2020), hotspot detection (Mousavi et al, 2021), traffic-related studies (Amegah et al, 2021;McFarlane et al, 2021), and health assessment (Tsou et al, 2021). This change is significant in transforming environmental governance, especially in historically underserved countries or regions, where access to the air quality data is insufficient to act on pollution trends (Pope et al, 2018).…”
Section: Introductionmentioning
confidence: 99%